Asuhan Keperawatan Pada Tn. I Pasien Risiko Perilakukekerasan Dengan Fokus Tindakan Pukul Bantal Untuk Mengontrol Emosi di RSJ Dr. Soeharto Heerdjan Jakarta - Eka Arif Setiawan; Christina Trisnawati; Rahaju Ningtyas (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Mental health for humans is the ability to overcome challenges, feel satisfied, and be independent are signs of mental health. The capacity to adapt to oneself, others, society and the environment is a sign of mental health. The risk of violent behavior is behavior that carries a risk of physically, emotionally or sexually harming oneself or others. Nursing actions that can be taken to control emotions in patients at risk for violent behavior include physical exercise by hitting a pillow. Physical exercise hitting a pillow is one way to channel anger or emotions into a pillow so you don't injure yourself or others. The Purpose: To determine nursing care for patients at risk of violent behavior with a focus on hitting pillows to control emotions. Method : The method used is descriptive with a case study approach to clients with risky problems of violent behavior. Results: Patients experienced an increase in channeling emotions, anger, or rage. Conclusion: Physical exercise hitting the pillow is indeed quite effective for channeling emotions because it doesn't hurt yourself, other people or the surrounding environment.